Fear of falling and activity restriction{ in older adults from the urban community of Londrina: a cross-sectional study - Fabiana Satiko Fucahori; Anália Rosário Lopes; Juliana Jaqueline Aparecida Correia; Carolina Kruleske da Silva; Celita Salmaso Trelha
Objective The objective of this study was to assess the fear of falling and restriction of activities in the elderly of the city of Londrina (PR). Materials and method A cross-sectional study was conducted with individuals over 60 years old of both sexes. They were interviewed at their home with the Falls Efficacy Scale International - Brazil the Survey of Activities and Fear of Falling in the Elderly a socio-demographic and health perception questionnaire. Results The participants were 38 elderly people (mean age 71.6 ± 6.1 years) with a prevalence of women (68.4%). The occurrence of a fall in the last year was reported by 44.7% of the elderly, and the prevalence of the fear of falling again by 56.3%. In the evaluation of the Falls Efficacy Scale, 97.4% of participants reported fear of falling in at least one of the activities while 55.3% had score ≥ 23 points showing high risk for falls. Fifty two percent of the elders restricted their activity due the fear of falling. Conclusion These results show a high frequency of fear of falling associated with restriction of activities and individuals with a high risk potential for falls. The evaluation of this data contributes to establishing indicators and development of preventive strategies and specific interventions for the elderly with fear of falling.